Bulk-mediated in-situ homogeneous photoalignment induced by reactive mesogen containing diphenylacetylene moiety. Issue 6 (2nd May 2020) - He, Rui; Wen, Pushan; Ye, Yang; Oh, Eunche; Kang, Shin-Woong; Lee, Seung Hee; Lee, Myong-Hoon
ABSTRACT: We designed and synthesised a reactive mesogen containing diphenylacetylene moiety in the mesogenic core and two polymerisable acrylate groups at both ends. By irradiating linearly polarised UV light on the conventional host LC mixture containing a small amount of the synthesised reactive mesogen in a sandwiched cell without an alignment layer, we demonstrated an in-situ photo-induced homogeneous alignment of liquid crystals without a pre-treated alignment layer, which was achieved by an irreversible polarisation-selective [2 + 2] photodimerization of diphenylacetylene moiety with linearly polarised UV irradiation at above the isotropic temperature of LC mixture. The resulting homogeneous alignment showed a superior initial dark state, negligible pretilt angle and excellent stabilities. Furthermore, the in-plane switching (IPS) LC cell prepared by this method exhibited a better dark state and electro-optic performance compared to that with conventional-rubbed polyimide alignment layer. The single photoirradiation process automatically resulted in a perfect alignment matching of optical axes between the top and bottom substrates in the LC cell, giving rise to an excellent dark state overcoming an intrinsic misalignment issue and complex fabrication process. The proposed in-situ alignment method is a promising candidate for cost-effective, green-manufacturing, and high-quality alignment technique in the manufacturing of high-resolution liquid crystal displays. GRAPHICAL ABSTRACT: